Sharia Economic Law in The Islamic Capital Market: Factors Influencing Selection and Decision-Making - Hardana, Ali; Abdul Razak, Dzulasjastri; Windari, Windari; Tussadiah, Halima; Nasution, Elga (Mu’amalah: Jurnal Hukum Ekonomi Syariah, 2024)
Investment is a compelling topic, especially in the capital market context. In Indonesia, which has the largest Muslim population in the world, the Islamic capital market plays a significant role in economic development under Sharia economic law. However, many Muslim investors still use conventional investment accounts, indicating a gap in understanding and adherence to Sharia principles. This study aims to examine the behavior of Muslim investors in making investment decisions based on Sharia principles and the factors influencing these decisions. This research employs a literature review method, with data from various journals, books, documentation, and internet sources over the past five years. The findings reveal that perceived behavioral control significantly influences investor decision-making, and attitudes toward perceived risk also impact investment decision-making. This study identifies a gap in the literature regarding Muslim investors' understanding of Islamic investment products and contributes new insights by integrating behavioral investment analysis with adherence to Sharia principles. These findings are expected to provide practical recommendations for developing the Islamic capital market in Indonesia and enhance Muslim investors' awareness and understanding of the importance of Sharia-compliant investments under Sharia economic law.